Hostage : [large type] a novel - Mackintosh, Clare (Thorndike Press large print thriller, adventure and suspense, 2021)
"From New York Times bestselling author Clare Mackintosh comes a claustrophobic thriller set over 20 hours on-board the inaugural nonstop flight from London to Sydney. Mina is trying to focus on her job as a flight attendant, not the problems with her five-year-old daughter back home, or the fissures in her marriage. But the plane has barely taken off when Mina receives a chilling note from an anonymous passenger, someone intent on ensuring the plane never reaches its destination: "The following instructions will save your daughter's life..." Someone needs Mina's assistance and knows exactly how to make her comply. When one passenger is killed and then another, Mina knows she must act. But which lives does she save: Her passengers...or her own daughter and husband who are in grave distress back at home? It's twenty hours to landing. A lot can happen in twenty hours"--